Characterization, antimicrobial and antitumor activity of superoxide dismutase extracted from Egyptian honeybee venom (Apis mellifera lamarckii) - Mohamed M. Abdel-Monsef; Doaa A. Darwish; Hind A. Zidan; Ahmed A. Hamed; Mahmoud A. Ibrahim (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background Superoxide dismutase is an important antioxidative stress enzyme which is found in honeybee venom and has a wide pharmaceutical and medical applications. Results We reported the purification and characterization of venom SOD from Egyptian honeybee Apis mellifera lamarckii and termed BVSOD. It was purified to homogeneity from the Egyptian honeybee venom. The purification procedures included crude extraction, DEAE-cellulose anion exchange column chromatography, and Sephacryl S-300 gel filtration column chromatography. The purified BVSOD is found to be homogeneous as investigated by native PAGE. It exhibited homodimeric structure with a molecular weight of native form of 32 kDa and subunits of 16.0 kDa. It displayed the maximum activity at pH 7.4. CuCl2, ZnCl2, and MgCl2 and elevated the activity of BVSOD, while CoCl2, FeCl2, and NiCl2 inhibited BVSOD activity. Potassium cyanide and hydrogen peroxide were most potent inhibitors for BVSOD activity suggesting that it is a Cu/Zn-SOD type. Conclusions The purified BVSOD is found to have antimicrobial and antitumor activities which can be used for various medical and clinical applications.